The Role of Minor Pilins in Assembly and Function of the Competence Pilus of Streptococcus pneumoniae - Oliveira, Vitor; Aschtgen, Marie-Stephanie; van Erp, Anke; Henriques-Normark, Birgitta; Muschiol, Sandra (Frontiers in Cellular and Infection Microbiology, 2021)
The remarkable genomic plasticity of Streptococcus pneumoniae largely depends on its ability to undergo natural genetic transformation. To take up extracellular DNA, S. pneumoniae assembles competence pili composed of the major pilin ComGC. In addition to ComGC, four minor pilins ComGD, E, F, and G are expressed during bacterial competence, but their role in pilus biogenesis and transformation is unknown. Here, using a combination of protein-protein interaction assays we show that all four proteins can directly interact with each other. Pneumococcal ComGG stabilizes the minor pilin ComGD and ComGF and can interact with and stabilize the major pilin ComGC, thus, deletion of ComGG abolishes competence pilus assembly. We further demonstrate that minor pilins are present in sheared pili fractions and find ComGF to be incorporated along the competence pilus by immunofluorescence and electron microscopy. Finally, mutants of the invariant Glu5 residue (E5), ComGDE5A or ComGEE5A, but not ComGFE5A, were severely impaired in pilus formation and function. Together, our results suggest that ComGG, lacking E5, is essential for competence pilus assembly and function, and plays a central role in connecting the pneumococcal minor pilins to ComGC.